Metal soft magnetic powder core and preparation method thereof
By using cold sintering-ultrasonic assisted method and heat treatment to generate a mixed insulating coating of iron oxide and copper oxide in the preparation process of metal soft magnetic powder core, the performance degradation caused by molding strain and high-temperature annealing treatment is solved, and the preparation of soft magnetic materials with high strength and excellent magnetic properties is achieved.
Patent Information
- Application Number
- CN202510017053.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-25
AI Technical Summary
The strain of existing metal soft magnetic powder cores causes a decrease in magnetic permeability and coercivity during the molding process, and high-temperature annealing treatment may lose the insulation effect, resulting in unstable performance and high production costs.
The mixed powder containing modified iron powder and mold release agent was subjected to temperature pressure pressing by cold sintering-ultrasonic assisted method, and then heat treatment was performed under oxygen-containing conditions to form a mixed insulating coating of iron oxide and copper oxide.
While reducing the pressing force and improving the pressing efficiency, the density, strength, resistivity and permeability of the magnetic core are improved, ensuring stable performance and reducing production costs.
Smart Images

Figure CN119694771A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal soft magnetic powder cores, and in particular to a metal soft magnetic powder core and a preparation method thereof. Background Art
[0002] Soft magnetic metal powder core (SMC) refers to a soft magnetic composite material formed into a certain shape by using micron-sized iron-based alloy powder coated with an insulating medium and then pressed and annealed. Figure 1 The general process flow of preparing metal soft magnetic powder core is: powder preparation → powder particle size ratio → powder insulation coating → pressing and molding → heat treatment.
[0003] Insulation coating is the most critical link, which plays a decisive role in improving the resistivity of magnetic powder core and reducing high-frequency loss. At present, the most commonly used coating processes are inorganic coating and organic coating. In addition, there is also a composite coating that combines the two.
[0004] Pressing molding is to press the coated alloy powder into various shapes as needed. Generally speaking, the greater the molding pressure, the denser the magnetic core is pressed, the greater its density and the greater the effective magnetic permeability. In addition, the pressed magnetic core green body requires sufficiently high strength to ensure that the shape stability and integrity can be maintained during subsequent processing. If the green body strength is insufficient, it is easy to cause deformation, cracking and other problems during the processing, thus affecting the performance and quality of the final product. Cold pressing is widely used in actual production because of its relatively simple process and easy to realize automated production. The pressing pressure of cold pressing is usually as high as 1.7-2.0Gpa. This is because high pressure can provide higher density for soft magnetic powder cores by promoting particle arrangement, deformation and even breakage, thereby improving the magnetic properties of the powder core.
[0005] In the preparation process of SMC, the strain generated during the molding process will reduce the magnetic permeability and coercivity of the material. In order to eliminate the strain generated by the magnetic powder during the molding process, high temperature annealing is inevitable. However, annealing may cause some insulating materials to decompose or change phases, resulting in loss of insulation effect. It is difficult for organic insulating materials to survive annealing temperatures above 400°C. Highly heat-resistant inorganic materials such as SiO 2 、Al 2 O 3 、MoO 3 、ZrO 2Wet chemical technology has been widely used to form an insulating protective layer. However, the inorganic insulating layer usually has weak adhesion to the powder and the process is complicated, which limits the stability of the process, the yield rate of SMC and the consistency of performance. For the cold pressing production method, the high pressure of GPa level can easily cause the powder particles to be squeezed and the insulating layer to break. On the other hand, the high production cost caused by the loss of large-tonnage presses and supporting molds is also unbearable for many powder core companies.
[0006] In addition, since most soft magnetic material components, especially high-power soft magnetic devices (such as the rotor and stator of the motor), will be subjected to a certain degree of dynamic environmental conditions such as vibration, impact and pressure during use; therefore, the development of soft magnetic materials with both high strength and excellent magnetic properties is a necessary condition for manufacturing high-performance soft magnetic devices.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] The purpose of the present invention is to provide a metal soft magnetic powder core and a preparation method thereof, which is conducive to preparing a soft magnetic material with both high strength and excellent magnetic properties.
[0009] The present invention is achieved in that:
[0010] In a first aspect, the present invention provides a method for preparing a metal soft magnetic powder core, comprising:
[0011] Cold sintering, under ultrasonic conditions, warm-pressing a mixed powder containing modified iron powder and a release agent to obtain a metal soft magnetic powder core green body; wherein the modified iron powder comprises iron powder and a coating layer coated on the surface of the iron powder, and the coating layer comprises copper, hydrated iron oxalate, hydrated copper oxalate and iron oxide;
[0012] Heat treatment: heat treating the metal soft magnetic powder core green body under oxygen-containing conditions to obtain the metal soft magnetic powder core.
[0013] In an optional embodiment, in the cold sintering step, the ultrasonic frequency is 15 kHz to 60 kHz, and the vibration amplitude is 80 μm to 120 μm.
[0014] In an optional embodiment, in the cold sintering step, the temperature is 100° C. to 120° C., the pressure is 400 MPa to 500 MPa, and the time is 8 s to 10 s.
[0015] In an optional embodiment, the preparation method of the modified iron powder includes: mixing a mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder with an oxalic acid solution, performing a coprecipitation reaction, separating the solid in the reaction liquid and drying it to obtain the modified iron powder.
[0016] In an optional embodiment, the mass ratio of deionized water, iron powder, sodium citrate, water-soluble iron salt and water-soluble copper salt in the mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder is 100:(240-260):(10-11):(1.8-2.2):(0.6-0.7), and the mass ratio of deionized water and oxalic acid in the oxalic acid solution is 100:(0.8-0.9);
[0017] And / or, the ratio of the oxalic acid in the oxalic acid solution to the total mass of the iron salt and the copper salt in the mixed solution is 1:(2.8-3.2);
[0018] And / or, the water-soluble iron salt is one or more of ferric nitrate, ferric chloride, and ferric sulfate;
[0019] And / or, the water-soluble copper salt is one or more of copper sulfate, copper chloride, and copper nitrate;
[0020] And / or, the iron oxide comprises Fe 2 O 3 and α-FeO(OH).
[0021] In an alternative embodiment, the drying temperature is less than 50°C.
[0022] In an optional embodiment, the release agent is zinc stearate, and the mass ratio of the release agent to the modified iron powder in the mixed powder is 0.5wt.% to 0.7wt.%.
[0023] In an optional embodiment, the temperature of the heat treatment step is 100° C. to 700° C., and the time is 3 h to 5 h.
[0024] In an optional embodiment, air is also introduced during the heat treatment step, and the air flow rate is 80 ml / min to 100 ml / min.
[0025] In a second aspect, the present invention provides a metal soft magnetic powder core prepared by the method described in any one of the aforementioned embodiments.
[0026] The present invention has the following beneficial effects:
[0027] The present application introduces ultrasonic assistance during cold sintering of iron powder, and can generate a mixed insulating coating layer of iron oxide and copper oxide in situ on the surface of powder particles during heat treatment, which is beneficial to reduce the pressing force and improve the pressing efficiency while improving the density, strength, resistivity and magnetic permeability of the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 Schematic diagram of the structure of metal soft magnetic powder core. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0031] An embodiment of the present invention provides a method for preparing a metal soft magnetic powder core, comprising:
[0032] Cold sintering, under ultrasonic conditions, warm-pressing a mixed powder containing modified iron powder and a release agent to obtain a metal soft magnetic powder core green body; wherein the modified iron powder comprises iron powder and a coating layer coated on the surface of the iron powder, and the coating layer comprises copper, hydrated iron oxalate, hydrated copper oxalate and iron oxide;
[0033] Heat treatment: heat treating the metal soft magnetic powder core green body under oxygen-containing conditions to obtain the metal soft magnetic powder core.
[0034] The embodiment of the present application adopts the cold sintering-ultrasound-assisted method, and the warm pressing can be completed in less than 10 seconds. While reducing the pressing force and improving the pressing efficiency, it is beneficial to improve the density and strength of the magnetic core. Specifically, the coating layer can reduce the surface energy of the iron powder particles, reduce the interaction force between the particles, make the powder easier to flow, and improve the shape of the iron powder particles, making them more regular and round, thereby reducing the friction and resistance between the particles and improving the fluidity of the powder; and the copper in the modified iron powder coating layer can improve the strength of the powder metallurgy green body. The reasons for the improvement mainly include material densification, metallurgical bonding strengthening, solid solution strengthening effect, and reduction of pores and defects. During cold sintering, the bound water in the hydrated oxalate is extracted as a local transient liquid transport phase. During the initial compaction process, the capillary force causes the particles to rearrange and promotes the interlocking between the particles, which is beneficial for the coating layer to uniformly fill the pores between the compacted particles through plastic deformation; in addition, the movement and rearrangement of the magnetic powder particles can be further promoted by ultrasonic vibration, thereby improving the density of the magnetic core. At the same time, the oxalate layer in the coating layer forms a co-continuous phase, which can promote strong cohesive interaction between the modified iron powder particles through chemical bonds. During the warm pressing process, there is good particle-particle contact between the modified iron powder particles, which is beneficial to improving the transverse fracture strength of the metal magnetic powder core.
[0035] In the embodiment of the present application, during the heat treatment, the hydrated ferric oxalate decomposes to produce Fe 2 O 3 Hydrated copper oxalate decomposes to produce CuO, and Cu will also be oxidized to CuO under high temperature and aerobic conditions. The in-situ generated mixed insulating coating containing iron oxide and copper oxide has high resistivity, which can effectively reduce losses. And because iron oxide is ferromagnetic, it can ensure that the metal soft magnetic powder core has a higher magnetic permeability.
[0036] In summary, the introduction of ultrasonic assistance during cold sintering of the modified iron powder and the in-situ generation of a mixed insulating coating layer of iron oxide and copper oxide on the surface of the powder particles during heat treatment are beneficial to reduce the pressing force and improve the pressing efficiency while improving the density, strength, resistivity and permeability of the magnetic core.
[0037] In an optional embodiment, in the cold sintering step, the ultrasonic frequency is 15 kHz to 60 kHz, and the vibration amplitude is 80 μm to 120 μm.
[0038] When the power and amplitude of the ultrasonic wave are beyond the above range, the density and strength of the metal magnetic powder core will be slightly improved.
[0039] In an optional embodiment, the temperature of the warm pressing step is 80°C to 100°C, the pressure is 400MPa to 500MPa, and the time is 8s to 10s.
[0040] Ultrasonic assistance in the cold sintering step can reduce the high pressure of GPa level to 400MPa-500MPa. It should be noted that if the temperature is too low, the bound water in the coating layer cannot be precipitated or precipitated too little, and the performance of the metal soft magnetic powder core cannot be effectively improved.
[0041] In an optional embodiment, the preparation method of the modified iron powder includes: mixing a mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder with an oxalic acid solution, performing a coprecipitation reaction, separating the solid in the reaction liquid and drying it to obtain the modified iron powder.
[0042] In an optional embodiment, the mass ratio of deionized water, iron powder, sodium citrate, water-soluble iron salt and water-soluble copper salt in the mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder is 100:(240-260):(10-11):(1.8-2.2):(0.6-0.7), and the mass ratio of deionized water and oxalic acid in the oxalic acid solution is 100:(0.8-0.9). If the amount of coating layer raw material used is too much, the coating layer in the modified iron powder will be too thick, which will reduce the magnetic permeability and increase the difficulty of pressing. It should be noted that the amount of each component used here is calculated in the form of no bound water.
[0043] And / or, the ratio of the oxalic acid in the oxalic acid solution to the total mass of the iron salt and the copper salt in the mixed solution is 1:(2.8-3.2);
[0044] And / or, the water-soluble iron salt is one or more of ferric nitrate, ferric chloride, and ferric sulfate;
[0045] And / or, the water-soluble copper salt is one or more of copper sulfate, copper chloride, and copper nitrate;
[0046] And / or, the iron oxide comprises Fe 2 O 3 and α-FeO(OH).
[0047] During the co-precipitation process, on the one hand, oxalic acid reacts with copper salts and iron salts to generate copper oxalate and iron oxalate precipitates, and on the other hand, metallic copper will be deposited. The mass ratio of iron powder, iron salt, copper salt and oxalic acid will affect the content of oxalate and copper in the modified iron powder, and thus affect the performance of the metal magnetic powder core product. Specifically, the amount of copper salt affects the strength of the green body after warm pressing. When the copper content is too high, it will reduce the toughness of the green body, causing the material to be more prone to fracture when impacted or subjected to external forces; the amount of iron salt, copper salt and oxalic acid affects the thickness of the modified coating layer after modification and the proportion of hydrated iron oxalate, and thus affects the thickness of the coating layer after subsequent heat treatment and the proportion of ferromagnetic iron oxide in the coating layer.
[0048] In an optional embodiment, the drying temperature is less than 50° C. In some embodiments, the drying can be performed at room temperature to reduce the loss of bound water.
[0049] In an optional embodiment, the release agent is zinc stearate, and the mass ratio of the release agent to the modified iron powder in the mixed powder is 0.5wt.% to 0.7wt.%.
[0050] In an optional embodiment, the temperature of the heat treatment step is 100° C. to 700° C., and the time is 3 h to 5 h.
[0051] In an optional embodiment, air is also introduced during the heat treatment step, and the air flow rate is 80 ml / min to 100 ml / min.
[0052] During the heat treatment process, sufficient oxygen is introduced to oxidize copper into copper oxide, while oxalate is thermally decomposed to produce copper oxalate and iron oxalate.
[0053] An embodiment of the present invention further provides a metal soft magnetic powder core, which is prepared by the method described in any one of the aforementioned embodiments.
[0054] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0055] Example 1
[0056] This embodiment provides a method for preparing a metal soft magnetic powder core, which specifically includes the following steps:
[0057] Step 1, surface modification of iron powder;
[0058] 1) Dissolve 10.5 g of sodium citrate in 100 ml of deionized water, then add 2 g of ferric nitrate, and then add 1 g of copper sulfate pentahydrate, and continue stirring until completely dissolved to form solution I;
[0059] 2) Add 250 g of iron powder (median particle size 100 μm) to solution I and stir for 5 min to form iron powder suspension II;
[0060] 3) Dissolve 1.2 g of oxalic acid dihydrate in 100 mL of deionized water to form solution III;
[0061] 4) adding solution III dropwise to the iron powder suspension II, stirring and mixing for 10 min, so that oxalate is co-precipitated from the solution to obtain mixture IV;
[0062] 5) The mixture IV is vacuum filtered and dried at room temperature to finally obtain modified iron powder.
[0063] Step 2: Add zinc stearate as a release agent to the modified iron powder and mix them evenly to obtain mixed magnetic powder, wherein the mass fraction of zinc stearate is 0.6 wt.%.
[0064] Step 3, performing warm pressing and using ultrasonic assistance;
[0065] The mold was used for compaction at 100 °C and a pressure of 500 MPa for 9 s, with an ultrasonic frequency of 40 kHz and a vibration amplitude of 100 μm.
[0066] Step 4: heat-treating the pressed green body to obtain a magnetic powder core product.
[0067] The annealing was performed in air at an air flow rate of 90 ml / min using a quartz tube furnace, placed at 100° C. for 4 h, and then cooled to room temperature.
[0068] Example 2
[0069] This embodiment provides a method for preparing a metal soft magnetic powder core, which is different from Embodiment 1 only in that the annealing temperature in step 4 is 300°C.
[0070] Example 3
[0071] This embodiment provides a method for preparing a metal soft magnetic powder core, which is different from Embodiment 1 only in that the annealing temperature in step 4 is 500°C.
[0072] Example 4
[0073] This embodiment provides a method for preparing a metal soft magnetic powder core, which is different from Embodiment 1 only in that the annealing temperature in step 4 is 700°C.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that step 1 is not performed, that is, the iron powder is not modified.
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that ultrasonic assistance is not used in step 3.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that no ferric nitrate is added in step 1.
[0080] Comparative Example 4
[0081] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that copper sulfate pentahydrate is not added in step 1.
[0082] Comparative Example 5
[0083] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 1 g of ferric nitrate is added in step 1.
[0084] Comparative Example 6
[0085] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 3 g of ferric nitrate is added in step 1.
[0086] Comparative Example 7
[0087] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 0.75 g of copper sulfate pentahydrate is added in step 1.
[0088] Comparative Example 8
[0089] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 1.25 g of copper sulfate pentahydrate is added in step 1.
[0090] Comparative Example 9
[0091] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 0.54 g of oxalic acid dihydrate is added in step 1.
[0092] Comparative Example 10
[0093] This comparative example provides a method for preparing a metal soft magnetic powder core, which is different from Example 1 only in that 0.75 g of oxalic acid dihydrate is added in step 1.
[0094] The properties of the metal soft magnetic powder cores prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.
[0095] Table 1
[0096]
[0097]
[0098] Compared with the green body compacted at medium temperature in comparative example 1, the transverse rupture strength of the green body compacted at medium temperature in example 1 is increased by 2 times. Further comparison of the metal soft magnetic powder cores after heat treatment in example 1 and comparative examples 1-2 shows that modifying the iron powder is beneficial to improving the density, strength and maximum magnetic permeability of the metal soft magnetic powder core, and can effectively reduce the iron loss. In the cold sintering step, the density, strength and maximum magnetic permeability of the prepared metal soft magnetic powder core can be further improved, and the iron loss can be further reduced under the presence of ultrasound. By comparing example 1 with comparative examples 3-10, it can be seen that the presence of copper and hydrated copper oxalate and the presence of hydrated iron oxalate and iron oxide in the coating layer are also crucial to the improvement of the density, strength and maximum magnetic permeability of the metal soft magnetic powder core and the reduction of iron loss. Furthermore, the component content also has an important influence on the improvement of the density, strength and maximum magnetic permeability of the metal soft magnetic powder core and the reduction of iron loss.
[0099] By comparing Examples 1-4, it can be seen that with the increase of the heat treatment temperature, the density, strength and maximum magnetic permeability of the prepared metal soft magnetic powder core gradually increase, but due to the high temperature, the insulating interface becomes thinner, which reduces the resistivity of the interface and leads to increased losses. Therefore, the heat treatment temperature is preferably 300°C to 500°C.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a metal soft magnetic powder core, characterized in that: include: Cold sintering, under ultrasonic assisted conditions, warm-pressing a mixed powder containing modified iron powder and a release agent to obtain a metal soft magnetic powder core green body; wherein the modified iron powder comprises iron powder and a coating layer coated on the surface of the iron powder, and the coating layer comprises copper, hydrated iron oxalate, hydrated copper oxalate and iron oxide; Heat treatment: heat treating the metal soft magnetic powder core green body under oxygen-containing conditions to obtain the metal soft magnetic powder core.
2. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: In the cold sintering step, the ultrasonic frequency is 15kHz to 60kHz, and the vibration amplitude is 80μm to 120μm.
3. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: In the cold sintering step, the temperature is 100° C. to 120° C., the pressure is 400 MPa to 500 MPa, and the time is 8 s to 10 s.
4. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: The preparation method of the modified iron powder comprises: mixing a mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder with an oxalic acid solution, performing a coprecipitation reaction, separating the solid in the liquid after the reaction and drying it to obtain the modified iron powder.
5. The method for preparing a metal soft magnetic powder core according to claim 4, characterized in that: The mass ratio of deionized water, iron powder, sodium citrate, water-soluble iron salt and water-soluble copper salt in the mixed solution containing sodium citrate, water-soluble iron salt, water-soluble copper salt and iron powder is 100:(240-260):(10-11):(1.8-2.2):(0.6-0.7), and the mass ratio of deionized water and oxalic acid in the oxalic acid solution is 100:(0.8-0.9); And / or, the ratio of the oxalic acid in the oxalic acid solution to the total mass of the iron salt and the copper salt in the mixed solution is 1:(2.8-3.2); And / or, the water-soluble iron salt is one or more of ferric nitrate, ferric chloride, and ferric sulfate; And / or, the water-soluble copper salt is one or more of copper sulfate, copper chloride, and copper nitrate; And / or, the iron oxides include Fe2O3 and α-FeO(OH).
6. The method for preparing a metal soft magnetic powder core according to claim 4, characterized in that: The drying temperature is less than 50°C.
7. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: The release agent is zinc stearate, and the mass ratio of the release agent to the modified iron powder in the mixed powder is 0.5wt.% to 0.7wt.%.
8. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: The temperature of the heat treatment step is 100° C. to 700° C., and the time is 3 h to 5 h.
9. The method for preparing a metal soft magnetic powder core according to claim 1, characterized in that: Air is also introduced during the heat treatment step, and the air flow rate is 80ml / min to 100ml / min.
10. A metal soft magnetic powder core, characterized in that: Prepared by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Amorphous soft magnetic composite magnetic powder core densification pressing method and equipment
CN120072505A
Preparation method of copper-plated soft magnetic composite material, soft magnetic composite material and application of soft magnetic composite material
CN122177615A
Preparation methods of copper-plated soft magnetic composite materials, soft magnetic composite materials and their applications
CN122177615B